The effect of basal–bolus therapy varies with baseline 1, 5‐anhydroglucitol level in people with Type 2 diabetes: a post hoc analysis. Issue 9 (19th June 2018) - Heller, S.; Bowering, K.; Raskin, P.; Liebl, A.; Buchholtz, K.; Gorst‐Rasmussen, A.; Pieber, T. R.
Abstract: Aims: To investigate the impact of baseline 1, 5‐anhydroglucitol on the treatment effect of basal–bolus therapy in people with Type 2 diabetes. Methods: Post hoc analysis of onset 3, an 18‐week, randomized, phase 3 trial evaluating the efficacy and safety of fast‐acting insulin aspart in basal–bolus therapy (n = 116) vs. basal insulin‐only therapy (n = 120) in people with Type 2 diabetes. The estimated treatment difference in change from baseline in HbA1c was investigated for different cut‐off values of baseline 1, 5‐anhydroglucitol (2, 3, 4, 5 and 6 μg/ml). Results: The estimated treatment difference in change from baseline in HbA1c between basal–bolus therapy and basal insulin‐only therapy was statistically significantly greater in participants with baseline 1, 5‐anhydroglucitol ≤3 μg/ml (n = 34) vs. >3 μg/ml (n = 198) [estimated treatment difference (95% CI): −1.53% (−2.12; −0.94) vs. −0.82% (−1.07; −0.57); P‐ value for interaction = 0.03]. The estimated treatment difference became more pronounced when comparing participants with 1, 5‐anhydroglucitol ≤2 μg/ml (n = 15) vs. >2 μg/ml (n = 217) [estimated treatment difference (95% CI): −2.26% (−3.15; −1.36) vs. −0.85% (−1.08; −0.62); P‐ value for interaction = 0.003]. For cut‐off values ≥4 μg/ml, estimated treatment differences were numerically greater below the cut‐off compared with above, although the interaction terms were not statistically significant. Conclusion: This analysis indicates that people with Type 2 diabetes with low 1, 5‐anhydroglucitol have an added treatment benefit with basal–bolus therapy compared with people with higher 1, 5‐anhydroglucitol. Further research is needed to clarify any clinical utility of these findings. Clinical Trials Registry No: NCT01850615 What's new?: The onset 3 trial evaluated the efficacy and safety of adding mealtime fast‐acting insulin aspart to basal insulin in people with Type 2 diabetes. This post hoc analysis of onset 3 indicates that low 1, 5‐anhydroglucitol is predictive of basal–bolus treatment effect. The findings suggest that 1, 5‐anhydroglucitol measurements may be useful for identifying people with Type 2 diabetes who would most benefit from intensifying insulin therapy, but further research is needed to determine whether 1, 5‐anhydroglucitol adds clinical utility beyond that of HbA1c .